Influences of macro-institutional environment on packaging used in beef and chicken meat agribusiness systems. - Meira Caunetto, Mariela; de Souza, José Paulo (Ciências Sociais Aplicadas em Revista, 2022)
This article purposes to understand how the institutional regulation on packaging influences the beef and chicken meat Agribusiness Systems distribution segment in Brazil. This is justified by considering that packaging affects price competition and is also an important element in food safety. Based on New Institutional Economics theory, it shows how the rules define transaction relations in distribution in these chains, considering the specificities in terms of performance in the analyzed period (growing chicken and stagnant bovine). Based on qualitative research and through semi-structured interviews, it identified that the rules influence these meats distribution in the retail segment, showing a stronger packaging presence in chicken distribution and low participation in beef meat. In addition, the informal regulation is still present as a strong reference for distribution process, especially for beef, where the chains adjust to the levels of demand.